Overlap syndrome and systemic sclerosis: a case report - Valencia Caballero, Víctor (2009)
Introducction: Different characteristics from diseases can coexist in the mixed disease of the connective weave, unlike the syndrome of superposition or overlap, that is the presentation of several autoimmune diseases that fulfill their criteria diagnoses in a patient.Clinical case: We presented/displayed the case of a woman of 32 years tried by esclerodermia during four years, that in a new evaluation diagnosed lupus and polimiositis, well-known like superposition syndrome. We discuss to the particular characteristics of the sclerosis and their evolution to other immune diseases.